Comparative analysis of modern deformation and the newest motions of the Earth surface in the territory of Ukraine - Orlyuk, M. I.; Ishchenko, M. V. (Geofizicheskiy Zhurnal, 2019)
Currently, the data of the Global Navigation Satellite Systems (GNSS) are widely used in the field of navigation, geodesy, cartography and regional geodynamic studies, in particular, in monitoring the movement of lithospheric plates, etc. Further development and creation of local GNSS networks, as well as the long-term replenishment of databases regarding the determination of the coordinates of individual stations and the speeds of their movement allows obtaining reliable more detailed information on the current deformation of the Earth's surface. The article discusses the current deformation of the Earth’s surface based on the analysis of the Global Navigation Satellite Systems data from the GAO NAS of Ukraine in comparison with the heights of the UGK2012 quasi-geoid and the latest lineament zones and faults, as well as with the late Pliocene-Quaternary vertical movements of the Earth’s crust. According to the results of the analysis of high-precision coordinates of displacement vectors of permanent GNSS stations in the territory of Ukraine, deformation parameters of the Earth’s surface were obtained, areas of prevailing compression values — tension and left-right-side rotation of the Earth’s surface were identified, the boundaries between which can be drawn along the latest lineament zones and faults. The areas of the predominant stretching of the Earth’s surface correspond to the zones of the newest tectonic uplifts (Volyn-Podolsk and Periazov hills) and maximum amplitudes of the Pliocene-Quaternary movements and positive geoid anomalies, and the areas of prevailing compression are zones of tectonic descents (Polissian and Peridnieper lowland), minimal amplitudes of Pliocene-Quarternary movements and minor heights of the geoid. Four large modern geoblocks have been identified: North-West and North-East, which rotate clockwise, and South-West and South-East rotating counterclockwise. At a qualitative level, the mechanism of interconnection of modern and newest movements of the Earth’s crust, namely, the presence of the latest tectonic zones of uplifting and lowering with corresponding tensions and movements of its surface, on which modern tensions (and corresponding movements) are imposed that are associated with the tectonic movement of the Eurasian Plate in northeastern direction and the irregular rotation of the Earth.